Analisis Perubahan Besaran Listrik Pada Pemanas Induksi Menggunakan Inverter Setengah Jembatan - Anggara, Sandy; Herawati, Afriyastuti; Priyadi, Irnanda; Anggraini, Ika Novia (UNIB Press, 2020)
AbstrakNowadays induction heating has become one of the people's choices in the heating process both in industry and households. Induction heating technology is also growing. But the electrical quantities that change with the temperature changes in the induction heating process must also be analyzed. To make induction heating, we need a device that is capable of producing large electrical energy. This tool uses a 12 Volt DC voltage, strong current 10 ampere and with a 120 watt input power. This induction heater is made using a half bridge inverter which generates heat through waves at high frequencies. The resonant frequency used is 25kHz. From the test obtained an average temperature increase of 134.5 ° C at the 600th second with a paper clip load and with a voltage of 3.33 Volts, a current of 0.15 A, a power of 0.56 watts, and a heat of 19.5J, and a test with a load nails obtained an average temperature of 136 ° C at 360 seconds with a voltage of 4.54 V, a current of 0.27 A, power of 1.12 watts, and a heat of 33.6JKata kunci : Pemanas Induksi, frekuensi, suhu, Solenoide.